Cerivastatin, an Inhibitor of HMG-CoA Reductase, Inhibits Urokinase/Urokinase-receptor Expression and MMP-9 Secretion by Peripheral Blood Monocytes - Ganné, Florence; Vasse, Marc; Beaudeux, Jean-Louis; Peynet, Jacqueline; François, Arnaud; Mishal, Zohar; Chartier, Antoine; Tobelem, Gérard; Vannier, Jean-Pierre; Soria, Jeannette; Soria, Claudine (Thrombosis and Haemostasis, 2000)
It is now recognised that acute myocardial infarction results from the rupture of atherosclerotic plaques. Lymphocytes and macrophages, which infiltrate rupture sites, contribute to plaque degradation by expressing urokinase (u-PA) bound to cell membrane by urokinase receptor (u-PAR) and by secreting metalloproteinase MMP-9.We have previously demonstrated that the uptake of oxidised LDL (ox-LDL) by monocytes induces an increase of u-PA and u-PAR expression. The present study shows that the expression of u-PA and u-PAR induced by ox-LDL on monocyte surface is suppressed by cerivastatin (a synthetic inhibitor of HMG-CoA reductase, Bayer) from 2 nM. This leads to reduced plasmin generation and monocyte adhesion to vitronectin. Furthermore, higher concentrations of cerivastatin (50-100 nM) reduce the expression of u-PA and u-PAR on unstimulated monocytes. It also inhibits MMP-9 secretion but has no effect on TIMP-1 secretion, suggesting that the decrease in MMP-9 has a real protective effect on plaque stabilisation. The inhibitory effect of cerivastatin on u-PA expression and MMP-9 secretion can be explained by the inhibition of NF-kappa B translocation into the nucleus, as shown by immunofluorescence. As farnesyl-pyrophosphate reverses the effect of cerivastatin, it is postulated that these effects could also be due to the inhibition of Ras prenylation. This was confirmed by confocal microscopy, which shows the Ras delocalisation from the monocyte membrane. The cerivastatin-induced effects on monocyte functions could explain, at least in part, the protective effect of this drug against atherothrombotic events.
Keywords: HMG-CoA reductase inhibitor; urokinase; metalloproteinase; atherothrombosis; monocyte